Achieving real equality in health and social care: IENE9 project, a work in progress for LGBT+ people - Lopez-Villegas, R.; Rocamora-Perez, P.; Pezzella, A.; Dudau, Victor; Kouta, Christiana; Nielsen, D.; Baiocco, R.; Kuckert-Wöstheinrich, Andrea; Papadopoulos, R. (My University, 2020)
Background Issues with professional conduct and discrimination against Lesbian, Gay, Bisexual, Transgender (LGBT+) people in health and social care, continue to exist in most EU countries and worldwide. Objectives The project IENE9 titled: “Developing a culturally competent and compassionate LGBT+ curriculum in health and social care education” aims to enable teacher/trainers of theory and practice to enhance their skills regarding LGBT+ issues and develop teaching tools to support the inclusion of LGBT+ issues within health and social care curricula. The newly culturally competent and compassionate LGBT+ curriculum will be delivered though a Massive Open Online Course (MOOC) which is aimed at health and social care workers, professionals and learners across Europe and worldwide. Results We have identified educational policies and guidelines at institutions teaching in health and social care, taken into account for developing the learning/teaching resources. The MOOC will be an innovative training model based on the Papadopoulos (2014) model for “Culturally Competent Compassion”. The module provides a logical and easy to follow structure based on its four constructs 'Culturally Aware and Compassionate Learning', 'Culturally Knowledgeable and Compassionate Learning', 'Culturally Sensitive and Compassionate Learning', 'Culturally Competent and Compassionate Learning'. Conclusions Specific training may result in better knowledge and skills of the health and social care workforce, which helps to reduce inequalities and communication with LGBT+ people, as well as diminishing the feelings of stigma or discrimination experienced.